MOMENTUM STRATEGIES AND TRADING VOLUME TURNOVER IN MALAYSIAN STOCK EXCHANGE - Husni, Tafdil (Jurnal Widya Manajemen & Akuntansi, 2006)
Using daily data on the Main Board of the Malaysian stock market from January 1988 to October 2002 and employing the strategy quite similar to Jegadeesh and Titman (1993) with some modifications, this study provides evidence on momentum strategy. That is strategy of buying stocks with high returns (winners) over the previous two and three months and selling stocks with low returns (losers) over the same period. The average differences between winner portfolios and loser portfolios in test period are 2.1% and 4.65 % in favor of winners, respectively. The result of this study is consistent with prediction of the under reaction hypothesis. This study also analyzes the relationship between momentum strategies and trading volume turnover (number of shares traded divided by the number of shares outstanding). The study reveals that momentum profits are more pronounced among high trading volume turnover stocks.